Trends in the Offshore Distribution and Relative Abundance of Beaufort Sea Belugas, 1982–85 vs 2007–09 - Harwood, Lois A.; Kingsley, Michael C.S. (ARCTIC, 2013)
We used systematic strip-transect aerial surveys to examine the distribution and relative abundance of surfaced belugas in the offshore Beaufort Sea in late August of 1982, 1984–85, and 2007–09. Belugas were seen throughout the offshore area in both survey series, on 114 of 149 transects (76.5%). They were common over the continental shelf offshore of the Tuktoyaktuk Peninsula and within 30 km seaward of the Mackenzie River estuary, but they were also seen in most other offshore habitats surveyed. The distribution of belugas had a similar pattern in both series, but the number of surfaced belugas counted was higher in the 2000s than in the 1980s. In total, 305 belugas (145 sightings, mean group size 2.1) were observed on-transect in 20 858 km2 of surveying in the 1980s, and more than three times that number (1061) were observed in a similar area (19 829 km2) during the 2007–09 survey series (378 sightings; mean group size 2.6). Population growth alone, though probably not sufficient to explain the changes observed in relative abundance between decades, could be partly responsible for the apparent increase in belugas. The most plausible explanation is that the offshore became more attractive to belugas in the 2000s, because of either a decrease in the intensity or extent of industrial activity or changes to the marine ecosystem related to climate warming, or both. Nous avons utilisé des levés aériens systématiques par transects en bandes pour examiner la répartition et l’abondance relative des bélugas faisant surface au large de la mer de Beaufort à la fin d’août 1982, d’août 1984 à 1985 et d’août 2007 à 2009. Des bélugas ont été aperçus au large dans les deux séries de levés et ce, dans 114 des 149 transects (76,5 %). Les bélugas étaient courants au large du plateau continental de la péninsule Tuktoyaktuk ainsi que dans un rayon de 30 km du côté mer de l’estuaire du fleuve Mackenzie, bien qu’ils aient également été aperçus dans la plupart des autres habitats étudiés au large. Dans les deux séries, la ...